HUBUNGAN KECERDASAN SPIRITUAL, EMOSIONAL, DAN INTENSITAS PEMBINAAN DENGAN KEBIASAAN BERPIKIR REFLEKTIF GURU DALAM MENGATASI MASALAH SISWA - Suhifatullah, M. I.; Darmojo, Hardjito S (Dharmas Education Journal (DE_Journal), 2024)
This study was conducted to measure the level of relationship between spiritual intelligence (X1), emotional intelligence (X2) and coaching intensity (X3) with teachers' reflective thinking habits in overcoming student problems (Y), both simultaneously and simultaneously. This study uses quantitative correlational methods with survey techniques. The sample was determined using the Slovin formula with an error allowance of 5%, so that a sample size of 125 people was obtained from a population of 181 teachers. To obtain data, a questionnaire instrument was used whose validity and reliability values ​​have been tested. The results of the research show that: (1) there is a strong positive relationship between spiritual intelligence and teachers' reflective thinking habits in dealing with student problems, based on the value of ry.1 = 0.562 > rtable (rttable = 0.176 at α = 0.05 and rtable = 0.230 at α = 0.01). (2) there is a strong positive relationship between emotional intelligence and teachers' reflective thinking habits in dealing with student problems, based on the value of ry.1 = 0.594 > r table (rt table = 0.176 at α = 0.05 and r table = 0.230 at α = 0.01 ). (3) there is a strong positive relationship between coaching intensity and teachers' reflective thinking habits in dealing with student problems, based on the value of ry.1 = 0.643 > rtable (rttable = 0.176 at α = 0.05 and rtable = 0.230 at α = 0.01 ). (4) there is a strong positive relationship between spiritual intelligence, emotional intelligence and coaching intensity simultaneously with the teacher's reflective thinking habits in dealing with student problems, based on the value of ry.1 = 0.701 > r table (rt table = 0.176 at α = 0.05 and r table = 0.230 at α = 0.01).